Persepsi Nelayan Tentang Manfaat dan Kondisi Ekosistem Laut Tropis di Taman Wisata Perairan Gili Matra, Kabupaten Lombok Utara - Febiliyadi, Aqidatul; Wardani, Niramaya Kusuma; Buhari, Nurliah (Jurnal Ilmu Kelautan Lesser Sunda, 2024)
Gili Matra National Conservation Area has potential ecological resources that the general public can utilize, such as coral reefs, seagrass beds, and mangroves. The purpose of the study was to determine the community's perception of the benefits and conditions of the coral reef, seagrass and mangrove ecosystems in Gili Matra Aquatic Tourism Park, North Lombok Regency. Data was collected through survey techniques and direct interviews with respondents using prepared questions (questionnaires). The results showed that the perception of people who work as fishermen about the condition of coral reefs, mangroves, and seagrass ecosystems is better in 2014 than in 2022, this is influenced by several threats such as human activities.